Insights into the Impact of Bankruptcy's Public Record on Entrepreneurial Activity: Evidence from Economic Experiments - Uwe Dulleck; Nicola J. Howell; Ann-Kathrin Koessler; Rosalind F. Mason (SSRN, 2018)
Many Anglo-American jurisdictions aim to provide debtors with a 'fresh start' after a personal bankruptcy. However, we query the extent to which debtors can achieve a fresh start if records of individual bankruptcies are publicly available, with no restrictions on their use. To inform the legal policy question of whether bankruptcy records should be publicly available, we study the effect of the availability of bankruptcy records, compared to their non-existence, in an economic experiment. The experiment allows us to identify empirically the effect that the exposure of bankruptcy history has on the behaviour of investors and debtors. Our exploratory research shows that the availability of bankruptcy records increases investment. Availability also increases repayment behaviour by debtors, but only if the debtor has no history of bankruptcy (non-return of payments). If, however, a debtor failed to return payments in the past, and this information is available, debtors show lower instances of return behaviour.
Keywords: K35; C90; D47; K20; 330; bankruptcy; investments; National Personal Insolvency Index; uncertainty; economic experiment; insolvency; public records